"Bangla Braille learning application" in smartphones for visually impaired students in Bangladesh. Issue 5 (4th July 2021) - Nahar, Lutfun; Sulaiman, Riza; Jaafar, Azizah
ABSTRACT: Android platform-based educational software for visually impaired students (VIS) are widely available, but very few of them are in Bangla. Due to the lack of low-cost Bangla Braille-based technologies, VIS depends on the traditional slate and stylus to learn Braille. This study proposes a Braille-based educational software, Bangla Braille Learning Application (BBLA), that helps VIS to learn Braille more effectively. Initially, interviews were conducted to identify the main challenges that VIS are facing; and based on the identified problem, BBLA is designed. The proposed interface layout is easy to distinguish that enables VIS to interact by touching the screen on smartphone. We have designed the software in a manner by which vibration and audio feedbacks are provided to users in response to their inputs. Interfaces were developed using JAVA programming language and Android development kit. The developed interfaces were evaluated by 6 advanced learners, 3 experts and 3 teachers through questionnaires; and by 30 VIS after using BBLA. Overall, results show that all respondents rated BBLA with a score of above 4.30 out of 5 in all the usability criteria (efficiency, learnability, memorability, error and satisfaction), indicating that BBLA is an effective Bangla Braille learning platform for VIS.